To solve the system of equations using substitution:
-
The given equations are: \[ x + y = 34 \quad \text{(1)} \] \[ 6x - y = 15 \quad \text{(2)} \]
-
Start by solving equation (1) for \(y\): \[ y = 34 - x \]
-
Substitute this expression for \(y\) into equation (2): \[ 6x - (34 - x) = 15 \]
-
Simplify the equation: \[ 6x - 34 + x = 15 \] \[ 7x - 34 = 15 \]
-
Add 34 to both sides: \[ 7x = 49 \]
-
Divide by 7: \[ x = 7 \]
-
Now substitute \(x = 7\) back into the equation for \(y\): \[ y = 34 - 7 = 27 \]
Thus, the solution to the system of equations is: \[ (x, y) = (7, 27) \]
The correct response is (7, 27).